'Facing the Sun': Nature and Nation in Franco's 'New Spain' (1936–51). (January 2021) - Del Arco Blanco, Miguel Ángel; Gorostiza, Santiago
Abstract: This article examines the relation between nation and nature in Spain during the Spanish Civil War and post-war years. As in other European cases of fascist and parafascist regimes, the Francoist regime mobilised nature for political and nationalistic goals. Spanish nature embodied the essences of the 'true Spain' and was seen as key to the regeneration of the country. The regime assumed an agrarian discourse that identified the countryside and nature with the real essences of the nation. It adopted autarkic political, social and economic directives, closing the country upon itself in order to regenerate and purge away its sins, but also confident that the nation's nature was the basis for building a new empire. Highlights: Examines the relation between nation and nature during the Spanish Civil War and post-war. As other fascist and parafascist regimes Francoism used nature for nationalistic and political purposes. The countryside was portrayed by Francoism as the seed of the nation in opposition to decadent urban life. Forests, mountains, rivers, and seas were key to delineate the Francoist rebirth of Spain. Concludes that the mobilisation of nature was key to forge the Francoist national project.